Psychological Safety of Radiologic Science Students. - Aaron, Laura; Renfro, Mary Grace; McGuire, Cindy (Radiologic Technology)
Purpose To explore the psychological safety of students in radiologic science programs. Methods A revised version of the Psychological Safety in High Fidelity Simulation scale was sent to program directors of accredited radiography, sonography, radiation therapy, magnetic resonance imaging, and nuclear medicine technology programs to share with their students. Descriptive statistics, a 1-way analysis of variance, and paired t tests were conducted to determine differences in psychological safety. Results A significant difference in psychological safety scores was identified between the classroom and clinical learning environments (P < .001) with students having higher levels of psychological safety in the classroom. The psychological safety scores of senior students were significantly higher than those of junior students in the classroom setting (P = .03) and the clinical setting (P = .02), and the seniors' average overall psychological safety score was significantly higher than the juniors' score (P = .02). Discussion Psychological safety differs between the classroom and clinical settings and is generally higher in the classroom. In most instances, senior students had higher psychological safety scores than did junior students. Conclusion Understanding the effects of student level (junior vs senior) and learning environment (classroom vs clinic) can help educators incorporate strategies to improve the psychological safety of students in radiologic science programs.